Expression of uPA, tPA, and PAI-1 in Calcified Aortic Valves - Najlah Kochtebane; Abdullah Mossa M. Alzahrani; Aghleb Bartegi (Biochemistry Research International)
Purpose. Our physiopathological assumption is that u-PA, t-PA, and PAI-1 are released by calcified aortic valves and play a role in the calcification of these valves. Methods. Sixty-five calcified aortic valves were collected from patients suffering from aortic stenosis. Each valve was incubated for 24 hours in culture medium. The supernatants were used to measure u-PA, t-PA, and PAI-1 concentrations; the valve calcification was evaluated using biphotonic absorptiometry. Results. Aortic stenosis valves expressed normal plasminogen activators concentrations and overexpressed PAI-1 (u-PA, t-PA, and PAI-1 mean concentrations were, resp., 1.69 ng/mL ± 0.80, 2.76 ng/mL ± 1.33, and 53.27 ng/mL ± 36.39). There was no correlation between u-PA and PAI-1 (r=0.3) but t-PA and PAI-1 were strongly correlated with each other (r=0.6). Overexpression of PAI-1 was proportional to the calcium content of the AS valves. Conclusions. Our results demonstrate a consistent increase of PAI-1 proportional to the calcification. The overexpression of PAI-1 may be useful as a predictive indicator in patients with aortic stenosis.